2002
DOI: 10.1097/00007632-200211150-00007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dysphagia After Anterior Cervical Spine Surgery

Abstract: Dysphagia after anterior cervical spine surgery is a common early finding. However, it decreases significantly by 6 months. The minority of patients experience moderate or severe symptoms by 6 months after the procedure. Female gender and multiple surgical levels could be identified as risk factors for the development of postoperative dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
530
11
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(577 citation statements)
references
References 14 publications
16
530
11
20
Order By: Relevance
“…He presented a weakness of his upper extremities and his mJOA decreased from 15 preoperatively to 13 at 2-year follow-up. Some authors [18] reported a 20 % incidence of dysphagia at 6 months after corpectomy. In our series, only one patient presented a severe dysphagia, which resolved at 6 weeks.…”
Section: Clinical Improvementmentioning
confidence: 99%
“…He presented a weakness of his upper extremities and his mJOA decreased from 15 preoperatively to 13 at 2-year follow-up. Some authors [18] reported a 20 % incidence of dysphagia at 6 months after corpectomy. In our series, only one patient presented a severe dysphagia, which resolved at 6 weeks.…”
Section: Clinical Improvementmentioning
confidence: 99%
“…Complications were assessed by reviewing the patients' medical records (Table 2). Dysphagia was evaluated using the dysphagia score proposed by Bazaz et al [22]. We considered the occasional sensation of dysphagia with solid foods as moderate and frequent episodes as severe.…”
Section: Outcomes Assessmentmentioning
confidence: 99%
“…The subjective perception of overall outcome was rated by the patients at follow-up as excellent, good, moderate, or poor. The incidence of dysphagia was evaluated with the grading system of Bazaz et al [8] that defines four grades: none, mild, moderate, or severe dysphagia based on subjective symptoms calculated by distinct combinations of existing difficulties with liquid and solid nutrition.…”
Section: Clinical Outcomementioning
confidence: 99%